A Study of Transverse Diameter of The Lumbar Spinal Canal in Plain Radiograph in Population of Telangana, India - Yousuf Begum; Syed Rehan Ha?z Daimib; Syeda Ayesha Fatima; Syeda Khadija Fatima (Academia Anatomica International, 2020)
Background: The present study was conducted to determine Transverse diameter (inter-pedicular distances) of the lumbar spinal canal measured in plain antero-posterior radiograph of 140 subjects (80 males, 60 females) aged between 20 to 60 years in population of Telangana. Subjects and Methods : The present study was conducted in the department of Anatomy, in a teaching medical college and hospital in Hyderabad, Telangana, India. It comprised of antero-posterior plain radiographs of lumbar spine of 140 subjects, aged between 20 to 60 years. Transverse diameter of the lumbar spinal canal or inter-pedicular distances (IPD), and transverse diameter of the vertebral body was measured using electronic Digital Vernier calipers, and the ratio between transverse diameter of vertebral canal and transverse diameter of the corresponding vertebral body were analyzed. Results: Out of 140 patients, males were 80 and females were 60. The mean inter-pedicular distance (IPD) at L1 was 24.2 mm in males and 23.4 mm in females, and at L5 was 30.2 mm in males and 29.6 mm in females. Mean transverse diameter of lumbar vertebral canal (I.P.D) is minimum at L1 vertebra in both sexes. The maximum values of I.P.D were recorded for vertebra L5 for both sexes. The values of IPD are higher in male population in comparison to female counterparts. The mean width of the vertebral body is gradually increasing from L1 to L5. Ratio between transverse diameter of vertebral canal and transverse diameter of the corresponding vertebral body is seen to be constant (0.6)   at all lumbar level in both the sexes. Conclusion: Authors found that there is variation in the size of the lumbar vertebral canal between males and females. Even after the revolution of various imaging techniques like CT Scan, MRI, etc., the plain radiography remains the mainstay of investigative procedure particularly in rural setup.